Sistem Pemesanan Restoran Berbasis QR Code dan Kitchen Display System - Muhammad Irzan; Boy Yuliadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research was motivated by the ongoing manual food ordering process at the Bakmi Ayam Bangka Chandra Restaurant, resulting in service delays, potential recording errors, and a lack of integration between customers, cashiers, and the kitchen. This situation impacts operational efficiency and customer satisfaction levels. The objective of this research was to design and develop a web-based food ordering information system integrated with the Kitchen Display System (KDS) to improve the speed, accuracy, and effectiveness of the restaurant's service process. The research method used was a qualitative approach, with data collection techniques including observation, interviews, and literature review. The system was developed using the Waterfall method, encompassing the stages of needs analysis, system design, implementation, and testing. The designed system allows customers to place orders independently by scanning a QR code, while order data is sent in real time to the kitchen and cashier without manual recording. The result of this research is an integrated ordering system that accelerates service flow, reduces the risk of communication errors, and provides more structured transaction recording. Implementing this system improves restaurant operational efficiency, enhances service responsiveness, and optimizes order management.